Plasma adiponectin levels predict cognitive decline and cortical thinning in mild cognitive impairment with beta-amyloid pathology - Keun You Kim; Junghee Ha; Minae Kim; So Yeon Cho; Hyunjeong Kim; Eosu Kim; for the Alzheimer’s Disease Neuroimaging Initiative (Alzheimer’s Research & Therapy, 2022)
Abstract Background Blood adiponectin and leptin are adipokines that emerged as potential biomarkers for predicting Alzheimer’s disease (AD) owing to their strong connection with obesity. Although obesity affects the relation between beta-amyloid (Aβ) aggregation and cognitive decline, the longitudinal interactive effect of adipokines and Aβ on cognition and brain structures in humans remains unexplored. Hence, we investigated whether plasma levels of adiponectin and leptin are associated with future cognitive decline and cortical thinning across Aβ conditions (Aβ [+] and Aβ [−]) in individuals with mild cognitive impairment (MCI). Methods Of 156 participants with MCI from the longitudinal cohort study of Alzheimer’s Disease Neuroimaging Initiative (ADNI), 31 were Aβ (−) and 125 were Aβ (+) as determined by CSF analysis. The Alzheimer’s Disease Assessment Scale-Cognitive Subscale (ADAS-Cog) scores and the thickness of the parahippocampal and entorhinal cortices were used to evaluate cognition and brain structure, respectively. After stratifying groups by Aβ conditions, the association of cognitive and brain structural changes with baseline plasma levels of adiponectin and leptin was examined. Results Of the total 156 participants, 51 were women (32.7%). The mean age of participants was 74.5 (standard deviation 7.57), and the mean follow-up period was 54.3 months, without a difference between the Aβ (+) and (−) groups. After adjustment for confounders, higher plasma adiponectin levels were associated with a faster increase in ADAS-Cog scores, indicating faster cognitive decline under the Aβ (+) condition (beta = 0.224, p = 0.018). Likewise, participants with higher plasma adiponectin presented faster cortical thinning in the bilateral parahippocampal cortices under the Aβ (+) condition (beta = − 0.004, p = 0.012 for the right side; beta = − 0.004, p = 0.025 for the left side). Interestingly, plasma adiponectin levels were not associated with longitudinal ADAS-Cog scores or cortical thickness in the Aβ (−) condition. Plasma leptin levels were not predictive of cognition or cortical thickness regardless of Aβ status. Conclusion Plasma adiponectin can be a potential biomarker for predicting the speed of AD progression in individuals with Aβ (+) MCI.